An innovative approach to addressing gender-based violence and adverse childhood experiences: An evaluation of the Alliance against Violence and Adversity (AVA) community agency internship program - Ashley Stewart-Tufescu; Stefan Kurbatfinski; Kharah Ross; Carrie Pohl; Ian D. Graham; Nicole Letourneau (Child Protection and Practice)
Background: Gender-based violence (GBV) and Adverse Childhood Experiences (ACEs) are associated with numerous detrimental health, social and economic impacts across the life course. Despite overwhelming evidence of GBV and ACEs as global health concerns, current approaches to prevent and respond to GBV and ACEs have been insufficient to address these problems. Drawing on evaluation and implementation research, innovations in GBV and ACEs training may help solve this problem. This study evaluated the Community Agency Internship Program (CAIP) of the Alliance against Violence and Adversity (AVA), a health research training platform that funds graduate student interns in community agencies focused on GBV and ACEs interventions in Canada. This evaluation focused on interns’ and community agency leaders’ self-reported perspectives of: the interns’ tasks and activities conducted during the internship, barriers and challenges, benefits and impacts, and satisfaction with CAIP. Methods: A pilot evaluation employed survey data collected between 2022 and 2024. Nine interns and four community agency leaders completed surveys at the conclusion of the CAIP placement. Quantitative and qualitative data were analyzed using descriptive statistics and deductive thematic analysis, respectively. Results: The CAIP positively impacted interns’ and leaders’ professional practice, goals, and personal growth, with most reporting high satisfaction with the program. Interns became comfortable with the pace of community-based work and engaging with diverse community members. Community agency leaders reported readiness to integrate research within their organizations and emphasized how the CAIP provided them with resources to engage in research and evaluation of their practice and implementation of services. Conclusions: The AVA CAIP promoted community agencies’ engagement in evaluation activities, and increased reciprocal learning about uptake, dosage, and maintenance of innovative programs to optimize service delivery to address the crisis of GBV and ACEs in Canada.